Tanggung Gugat Direksi Terhadap Audit Laporan Keuangan PT Garuda Indonesia (Persero) Tbk Ditinjau Melalui Doktrin Fiduciary Duty - Dimas Seandy Frinaldo; Iswi Hariyani; Bhim Prakoso (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
Abstract: Article 92 paragraph (1) of the Limited Liability Company Law states that the board of directors accepts the mandate of the company to take care of the interests of the company, as well as its duties and functions in running the company (fiduciary duty). The responsibility of the board of directors in managing the company can have consequences if the board of Directors has bad faith in carrying out its obligations. The study was conducted using normative juridical methods to find the liability of the board of directors to audit the Financial Statements of Limited Liability Companies. Such as the case of the Directors of PT Garuda Indonesia (Persero) Tbk who were negligent and bad faith in making financial statements in 2018. The implementation of PSAK 23 in the presentation of the financial statements for the 2018 financial year has been based on Generally Accepted Accounting Principles, but the work between PT Garuda Indonesia (Persero) Tbk and PT Mahata Aero Teknologi has not been recognized as revenue because it can cause confusion and mislead the company. Based on Article 97 paragraph (3) and (4) of the Limited Liability Company Law, each member of the board of directors bears full responsibility personally and/or jointly and severally for the losses of the company if the person concerned is guilty or negligent in carrying out his duties. Legal implications in the event that the financial statements provided are incorrect and / or misleading, members of the Board of Directors and members of the Board of Commissioners are jointly and severally responsible for the injured party. Keywords: Responsibilities; Directors; Financial Statements.